Determinants of Non-performing Loans in Commercial Banks in Kenya - Esther , Irene Njeri (An Overview on Business, Management and Economics Research Vol. 5, 2023)
This chapter focuses on assessment of determinants of non-performing loans (NPLs) in commercial banks in Kenya. A loan is classified as nonperforming loan when the borrower fails to make scheduled payments of principal or interest for a period of 90 to 180 days. In Kenya, the trend of NPLs increased throughout the 1990s and prior years, causing many banks to fail and others to be placed under statutory supervision. The survivor banks and those founded subsequently discovered that inadequate loan management was a major cause of the severe blow. While the borrowers are to blame, the management of the collapsed institutions must share the blame for adopting poor lending policies, as several lacked smart new techniques of managing NPLs. However, improved credit risk management has reversed the trend of NPLs. Nonetheless, the percentages of gross NPLs to gross loans remain high, potentially leading to the collapse of more banks. The study's aims were to determine whether risk assessment methods, the level of borrowers' lack of awareness of items being supplied, risk management methods, economic conditions, and technical obsolescence all contribute to NPLs. To achieve these goals, primary data was gathered by distributing questionnaires to credit division staff at chosen banks. The information was examined and displayed in tables using the statistical method of spearman's correlation coefficient. The findings revealed that, of the five components evaluated, risk assessment methods had the highest correlation coefficient, making them the primary contributor to NPLs, followed by borrowers' lack of awareness of the products being offered, while risk management methods had the smallest contribution. The findings will give bank management increased knowledge on credit risk exposure and NPL control, resulting in increased profitability.